Al-Idrīsī and a Translation and Commentary About the Far East from His Nuzhat Al-Mushtāq - Sarıp, Muhammad Ashraf (Istanbul University Press, 2020)
This paper talks about the earliest Islamic knowledge on the Far East based on 8th – 12th century extant works on geography as well as travel accounts. It shows how pre-Islamic works on geography, e.g. the al-Ğuġrafyā of Ptolemy, the Sindhind of the Indians, and imperial practices of the pre-Islamic Persia, influenced the thinkers of medieval Islam. It offers a comprehensive overview on the development of Islamic geographical practices in the Middle Ages by consulting the works of Ibn Khurdādhbih (d. 912 CE), al-Marwazī (d. 887 CE), al-Ya‘qūbī (d. 897 CE), al-Nadīm (fl. 10th century), al-Khwārizmī (d. 850 CE), Al-Mas‘ūdī (d. 956 CE), al-Sīrāfī (fl. 10th century), ibn Ḥauqal (d. 977 CE), al-Muqaddasī (d. 991 CE), al-Andalusī (d. 1070 CE), among others. The paper highlights the parts that cover the Far East in Nuzhat al-Mushtāq fi ikhtirāq al-āfāq, also known as the Book of Roger, a magnum opus written by a 12th century Sicilian scholar, al-Sharīf al-Idrīsī. The sections of Nuzhat al-Mushtāq that talk about the Far East are translated from its original language to English. An excerpt from the translation is included in this paper. The progression of Nuzhat al-Mushtāq, which started upon the invitation of King Roger II of al-Sharīf al-Idrīsī to his court in Palermo and the commissioning of the latter to make a map of the world, as well as the biography of al-Sharīf al-Idrīsī are also presented in this endeavor.

Bu çalışma, 8’inci ve 12’inci yüzyıllar arasından günümüze ulaşan gerek coğrafya ve haritacılık alanındaki çalışmalara gerekse seyahatnamelere dayanarak Uzak Doğu’ya dair ilk İslâm bilgi birikimini konu edinmektedir. Bu çerçevede, Batlamyus Coğrafyası, Hintlilerin Sindhindi ve İslâm-öncesi Pers emperyal girişimleri gibi coğrafya temalı İslâm-öncesi çalışmaların Orta Çağ İslâm düşünürlerini nasıl etkilediği ortaya konulmaya çalışılmıştır. İbn Ḫurdâzbih (ö. 912), Mervezî (ö. 850), Ya’kûbî (ö. 897), en-Nedîm (10. yy.), Ḫarizmî (ö. 850), Mes’ûdî (ö. 956), Sîrâfî, (10.asır), Ibn Havḳal (ö. 977), Muḳaddesî (ö. 991) ve Endelüsî’nin (ö. 1070) eserlerine, bunlarla sınırlı olmamak kaydıyla, başvurarak Orta Çağ İslâm coğrafya pratikleri ve haritacılık geleneğinin gelişimine ilişkin genel bir değerlendirme sunulmuştur. Çalışmamızda Sicilyalı âlim Şerîf el-İdrîsî tarafından 12’inci yüzyılda kaleme alınmış ve Roger’ın Kitabı olarak da bilinen şaheser Nuzhatü’l-Müştâḳ fî iḫtirâḳ el-âfâḳ’ın bazı bölümlerine özel vurgu yapılmaktadır. Çalışma kapsamında, Nuzhat’ın Uzak Doğu temalı bölümleri Arapça aslından İngilizce’ye tercüme edilmiştir. Çeviriden bir seçme parçası bu makaleye dahil edilmiştir. Bu bağlamda, Nuzhat’ın Kral II. Roger’ın Şerîf el-İdrîsî’yi Palermo’daki sarayına davetinden başlayıp kendisini bir dünya haritası çıkarmakla görevlendirmesiyle sürüp giden akışı sergilenmiştir.
El-İdrîsî ve Nuzhatü’l-Müştâḳ Adlı Eserinin Uzak Doğu ile İlgili Bölümünün Çeviri ve Yorumu
Keywords: Islamic Geography; Islamic Cartography; Nuzhat al-Mushtāq; Book of Roger; King Roger II; al-Ğuġrafiyā; Ptolemy; Sindhind; al-Sharīf al-Idrīsī; Far East